Fostering Organizational Learning through Corporate Culture, and Core Competences - James, Oguta; Andrew, Kimwolo (American Journal of Social Sciences and Humanities, 2022)
The paper examines the relationship between corporate culture, core competences and organizational learning among manufacturing firms in Uganda. Using a self-administered questionnaire and interview guide, this research gathered quantitative and qualitative data from 410 Ugandan manufacturing businesses in Uganda. A cross-sectional explanatory survey design was employed to study the nature of reality. To test the hypothesis, regression analysis was performed, while content analysis was used to evaluate qualitative data. According to the results, corporate culture has a positive influence on organizational learning, and core competencies also have a positive effect on organizational learning. The results supported the theoretical foundations of organizational learning and resource-based view theories. As a result of the findings, manufacturing firms may increase the influence of strategic leadership on organizational learning by promoting cultures that emphasize employees' desire to improve and learn, openness, creativity, teamwork, interaction with others, open dialogue, long-term orientation, and mutual trust. Furthermore, manufacturing firms should guarantee that capabilities are built inside their organizations. The results might help Chief Executive Officers (CEOs) and policymakers develop strategies and policies to boost organisational learning among manufacturing firms. This research contributes to our knowledge of the influence of strategic leadership aspects on organizational learning in manufacturing firms, particularly in a developing country like Uganda.